The Iraqi conservative right and the reproduction of political identity - hadi , hussam rashed (The International and Political Journal, 2025)
The Iraqi political landscape is undergoing rapid and intricate transformations, fueled by interwoven internal, regional, and international dynamics. This study delves into the pivotal role of conservative currents, which have historically solidified their presence in shaping collective consciousness and guiding political action in Iraq. It explores the imperative for these currents to redefine their political identity amidst the crucible of contemporary challenges, ranging from the throes of democratic transition to the repercussions of sectarian conflicts and the far-reaching implications of globalization. The research probes how the Iraqi conservative right is reconfiguring itself, specifically discerning whether it is in the process of forging a moderate 'third path' that transcends the excesses of Islamist extremism and the tenets of revolutionary leftist ideologies, or if it faces the peril of further isolation or ossification within its traditional frameworks. By deconstructing the concept of conservative rights, elucidating its historical roots, delineating its distinctions from the left, and reviewing its stances on societal, religious, and national issues, this work aims to offer a profounder understanding of its ongoing transformative dynamics. Ultimately, this research enriches the field of Iraqi political studies by presenting novel insights into the dynamics of political identity in post-change Iraq, highlighting the potential for the crystallization of innovative pragmatic approaches to confront current challenges Conservatism is an approach to political life that emphasizes wisdom, commitment, responsibility, tradition, and gradual change. Therefore, it can be described as political practice without theory.